Desarrollo de una metodología de monitoreo y control de la calidad de agua en la inyección de geles de dispersión coloidal en un campo ubicado en la cuenca del Valle superior del Magdalena (2020)
In this work, a detailed analysis of the historical data from production water of Field A since 2009 was performed, using the software created "Intelligent Water Management for CEOR Operations". It was possible to obtain trends, max and minimum values in parameters of high importance for CEOR, such as Salinity, Dissolved iron, pH, Hardness, dissolved oxygen, among others using this software. The status of the operation of the water facility was diagnosed using hidrogeochemical analysis in order to determine the reduction of these parameters in the process. Comparing Ecopetrol with other companies, such as YPF and CNPC, was possible with a detailed benchmarking; which include best practices and innovative technology for the surveillance and control of these types of projects. Laboratory tests was pivotal in order to determine the max allowed values for the properties mentioned before, and the response variable in all of the experiments was the percentage of reduction of viscosity in the polymeric solution. The results allow concluding that the cation that affects more the viscosity is the Magnesium, establishing the following limits: Hardness 1480 ppm, Calcium Hardness 1020 ppm, Sulfates 36 ppm, Carbonates 990 ppm. Barium 54 ppm, Chloride 9800 ppm, Calcium 500 ppm, Magnesium 100 ppm, Strontium 32 ppm. Potassium 110 ppm, pH lower than 8, dissolved oxygen 32 ppb and dissolved iron 225 ppb.